Orbital Pseudotumor as an Extrahepatic Complication of Chronic HCV Infection - Owen Huang; Tina Shah; Divya Sundarapandiyan; Matthew J. Akiyama (Case Reports in Infectious Diseases)
We present a patient who was admitted for eye swelling, pain, and discharge, with CT orbits with contrast demonstrating inflammation and enlargement of the lacrimal glands and surrounding tissue. He was found to have an HCV infection for unknown duration upon further investigation. All other workup (autoimmune, rheumatic, and infectious) was unrevealing. The patient was diagnosed with orbital pseudotumor as an extrahepatic complication of chronic HCV infection, and he was managed with prednisone which dramatically decreased his eye swelling and pain. Steroid treatment may serve as a bridge to suppress symptoms of extrahepatic manifestations, especially in ocular cases, while HCV-infected patients await treatment to eradicate their HCV infection.